The Influence of CYP2C19 Gene Polymorphism on Selective Serotonin Reuptake Inhibitors In Patients with Major Depressive Disorder: A Pharmacogenetic Prospecting Approach - Urbaningrum, Lestari Mahardika; Hermosaningtyas, Anastasia Aliesa; Kasasiah, Ahsanal; Rahmasari, Ratika; Raekiansyah, Muhareva; Hartanto, Adrian; Malau, Jekmal (Faculty of Medicine, Universitas Diponegoro, 2024)
Major Depressive Disorder (MDD) is a chronic disorder characterized by at least a two-week-long major depressive episode. Selective Serotonin Reuptake Inhibitors (SSRIs) remain the primary prescribed antidepressants to treat MDD. However, SSRIs themselves are found to be ineffective in some individuals or may even lead to adverse side effects. These variable responses have been linked to the drug being metabolized by CYP2C19, which exhibited various polymorphisms. Understanding how gene polymorphism affects drug metabolism is essential since these insights can revolutionize clinical practice, allowing for more precise and personalized treatment approaches that optimize efficacy while minimizing side effects. This issue is particularly pertinent in Indonesia, where research in this area lags behind the pressing need for such studies. In this review, the impact of CYP2C19 polymorphism on the effectiveness of SSRI class drugs, namely citalopram, escitalopram, and sertraline, are explored. Nine relevant articles related to the topic have been studied in Japan, China, Turkey, Russia, Scandinavia, and Australia. The results concluded that CYP2C19 polymorphism can influence the metabolism of SSRIs (citalopram, escitalopram, and sertraline) due to its variability in enzyme activities, which includes both loss-of-function (*2, *3) and gain-of-function (*17) polymorphisms. Consequently, these genetic variations can lead to significant changes in drug efficacy and safety changes within individual patients. This review sheds light on the importance of considering genetic factors when prescribing SSRIs for MDD in the future treatment strategies.